Methodological grounds for researching the role of non-economic factors in the systemic development of society - Shavel, Sergei A. (Journal of the Belarusian State University. Sociology, 2019)
Considered are the methodological grounds for analyzing the non-economic factors of economic growth and systemic development of society. Studied are the semantics of the factor approach, sociological theories of factors determining the historical evolution of society, economic theories of the factors of production, modern factor paradigms. Explicated are such non-economic factors as social capital, human capital, archetypes and other elements of the collective unconscious.
Keywords: factor; factor paradigms; archetypes; motivation; determinism; social capital; human capital; innovations; psychological factors